The Role of Nutrition in COVID-19: Taking a Lesson from the 1918 H1N1 Pandemic. Issue 1 (January 2023) - Kahleova, Hana; Barnard, Neal D.
In looking for solutions to the COVID-19 pandemic, important lessons come from the H1N1 influenza pandemic of 1918–1919. During the H1N1 influenza pandemic, the soldiers had better outcomes than the civilian populations, but the best outcomes were reported by a Seventh-day Adventist seminary, where a plant-based diet was provided. The diet has been described as including grains, fruits, nuts, and vegetables. A few clinical trials have also assessed the role of nutrition in COVID-19. One study with almost six hundred thousand participants showed that those with a high consumption of fruits and vegetables had a reduced risk of COVID-19 of any severity by 9% and a reduced risk of severe COVID-19 by 41%. Another study in healthcare workers who were frequently exposed to COVID-19 in their clinical practice has demonstrated that those who reported being on a plant-based diet had a 73% lower risk of moderate-to-severe COVID-19. Based on the lessons from 1918 and the recent nutrition research in COVID-19, it seems plausible that a healthful plant-based diet may be a powerful tool to decrease the risk of severe COVID-19 and should be promoted as one of the public health safety measures.